Efektivitas Pemanfaatan Media Sosial Instagram oleh Diskominfo Kota Batam Sebagai Alat Untuk Menyampaikan Informasi Kepada Masyarakat - Anggraini, Prishilia; Cindoswari, Ageng Rara (SCIENTIA JOURNAL, 2024)
Social media is very important for the people of Batam City because it is useful in providing information quickly, efficiently and accurately through various communication channels used by organizations, companies and the government. Social media has become an important communication tool in the digital era, enabling the dissemination of information in real-time and reaching a wide audience. This research uses a qualitative method with a case study approach involving observation, content analysis, and interviews with Diskominfo and Instagram users in Batam City. The research results show that technological developments encourage Diskominfo to adopt Instagram as an effective and efficient communication tool in conveying important information to the public. Visual content such as infographics, videos and interactive stories can attract attention and increase public engagement. Consistent post scheduling strategies and the use of interactive features, such as live streaming and Q&As, also play an important role in increasing engagement. The challenges faced include increasing digital literacy and information accessibility for all levels of society. In conclusion, in an era of rapid technological development, Instagram has become a vital medium for the Batam City Diskominfo in supporting effective communication between the government and the community.